The legal nature of currency regulation - Бабін, Ігор; Вакарюк, Людмила (Studia Iuridica Toruniensia, 2017)
The article analyzes the legal nature of the institution of currency regulation with the system approach, because in post-Soviet Ukrainian science of financial law this problem was not yet been investigated. For most researchers of this problem is characteristic pure positivism, elementary approach to the institution of currency regulation, as an object of knowledge. The systems approach, from the point of view of the authors, seems to be most constructive and productive for the successful solution of the basic problems of the theory of financial and legal institutions in general and the institute of currency regulation in particular. According to an article, the authors attempt to investigate the properties of the institute of currency regulation, because the properties of institute of currency regulation are not than other, as the outward manifestation of one of the moments of the substance. In particular, the article analyzes the intrinsic properties of institute of currency regulation, such as its goal, the species specificity of the content and form of its precepts, hierarchy and structure. Also, no less important issue of research entities of the institute of currency regulation is the definition of the system and its special principles, the content of which is analyzed by the authors of this article.